Upaya Meningkatkan Kemampuan Mengenal Huruf Melalui Balok Huruf - Desy Ayu Refiani; Umayyah Umayyah; Uyu Mu’awwanah (UIN Sultan Maulana Hasanuddin Banten, 2019)
This study aims to improve the ability to recognize letters by using letter beam media in group B children at TK IT Afta Banten. The ability to recognize improved letters is to mention letters, show letters, and connect letters. This study was conducted because there were problems in recognizing letters in group B. This study employed classroom action research and conducted collaboratively between researchers and classroom teachers. The subjects of this study were 19 students of TK IT Afta Banten. The object of research in this study is to increase the ability to recognize letters using letter beam media. The data collection technique used observation and interviews. Meanwhile, for research instrument used a checklist observation. Based on the result findings it can be concluded that the ability to recognize the letters of group B children in TKIT Afta Banten can be improved using letter beam media in the process of playing media guessing letters in children's letters are made by groups and playing alternately then the child plays according to the teacher's instructions mention letters, show letters, and connect letters. The finding of study shows that the ability of students to recognize letters improve that is in the initial conditions of 59.78%, The finding of this study shows that there is an improvement from the first cycle was 73.53%, to the second cycle was 83.42%. Keywords: the ability to recognize letters, letter beam media, learning outcomesReferencesArikunto, S. (2012). Penelitian Tindakan Kelas. Jakarta: PT Bumi Aksara.Fatihah, N., & Difla Nadjih. (2017). Hubungan Pendidik Dan Terdidik Dalam Al-Quran. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 7(2), 73–86. Hasanah, H. (2018). Peningkatan Kemampuan Mengenal Lambang Huruf Melalui Metode Proyek Dan Media Bungkus Makanan Dan Minuman Ringan Pada Kelas B Di RA Riyadul Fata Tembongraja Kecamatan Salem Kabupaten Brebes. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 101–124.Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71.Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional bagi Siswa Raudlatul Athfal. Al Hikmah Proceedings on Islamic Early Childhood Education, 1, 103–112. Tuban: Program Studi PIAUD STAI Al Hikmah Tuban.Kurniawan, H. (2018). Pengembangan Lingkungan Belajar Literasi Untuk Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 45–56.Madyawati, L. (2016). Strategi Perkembangan Bahasa Pada Anak. Jakarta: Kencana.Martini, M., Biryati, B., & Wiyani, N. A. (2019). Peningkatan Kemampuan Mengenal Lambang Huruf Melalui Metode Proyek Dan Media Bungkus Ajaib Pada Kelas B2 Di TK Pertiwi II Banteran Kecamatan Wangon Kabupaten Banyumas. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 25–38.Mawadah, A. H. (2018). Pemanfaatan Big Book Sebagai Media Literasi Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 3(1), 57–72.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 9(1), 49–60.Sudjiono, A. (2010). Pengantar Statistik Pendidikan. Jakarta: PT Rajagrafindo.Taniredja, T., Pujiati, I., & Nyata. (2012). Penelitian Tindakan Kelas Untuk Pengembangan Profesi Guru Praktik. Praktis. Dan Mudah. Bandung: ALFABETA.